Neurosteroids and GABA-A Receptor Function - Wang, Mingde (Frontiers in Endocrinology, 2011)
Neurosteroids represent a class of endogenous steroids that are synthesized in the brain, the adrenals and the gonads and have potent and selective effects on the GABAA-receptor. 3α-hydroxy A-ring reduced metabolites of progesterone, deoxycorticosterone and testosterone are positive modulators of GABAA-receptor in a non-genomic manner. Allopregnanolone (3α-OH-5α-pregnan-20-one), 5α-androstane-3α, 17α-diol (Adiol) and 3α5α-tetrahydrodeoxy-corticosterone (3α5α-THDOC) enhance the GABA mediated Cl− currents acting on a site (or sites) distinct from the GABA, benzodiazepine, barbiturate and picrotoxin binding sites. 3α5α-P and 3α5α-THDOC potentiate synaptic GABAA-receptor function and activate delta-subunit containing extrasynaptic receptors that mediate tonic currents. On the contrary, 3β-OH pregnanesteroids and pregnenolone sulfate (PS) are GABAA-receptor antagonists and induce activation-dependent inhibition of the receptor. The activities of neurosteroid are dependent on brain regions and types of neurons. In addition to the slow genomic action of the parent steroids, the non-genomic and rapid actions of neurosteroids play a significant role in the GABAA-receptor function and shift in mood and memory function. This review describes molecular mechanisms underlying neurosteroid action on the GABAA receptor, mood changes and cognitive functions.